Beauty of Women in Life and Educational Space: Approaches of Metaanthropology and Androgyny-Analysis - Krylova, Svitlana; Khamitov, Nazip (Filosofiya osvity. Philosophy of Education, 2013)
Based on the contemporary trend of philosophy of sex and gender — androgyny-analysis, which is the method of investigation and deep correction of personality and relationships between man and woman, gender dimensions of beauty and their impact on the educational process are studied. The authors emphasize on beauty as a fundamental value of woman’s life-world. Androgynyanalysis investigates the external and the internal beauty of a woman — the beauty of world view, the beauty of acts and the beauty of relationships In androgyny-analysis which is ideologically rooted in meta-anthropology as theory of ordinary, ultimate and transcendent of human being, authors underline three basic strategies of interaction of existential masculinity and femininity in the inner world of the personality and in relationships between personalities: «existential sexism», «existential hermaphroditism» and the «existential androgynism». These strategies correlate with three fundamental dimensions of human existence, which are proposed in metaanthropology. Androgynism comprehends as harmony of spiritual and soulfulness in the inner world of personality and in interaction with other personalities and defines as the most expressive correlate of internal beauty in its gender manifestations, and therefore a factor of actualization the educational process.